Optimal Minimum Violation Control Synthesis of Cyber-Physical Systems Under Attacks - Niu, Luyao; Fu, Jie; Clark, Andrew (IEEE transactions on automatic control, 2021)
Temporal logic provides a rigorous and expressive way to model specifications for cyber-physical systems (CPS). Such systems, which are playing increasingly important roles in various domains, are also subject to malicious attacks initiated by intelligent adversaries. Malicious attacks may prevent the system from satisfying the desired specification. In this article, we introduce a control synthesis method to minimize deviations from the desired specification due to adversaries. We consider the scenario where the adversary has limited capability of observing the controller's strategy. We synthesize a minimum violation control strategy for a finite-state stochastic game under cosafe linear temporal logic constraints. We formulate a mixed-integer nonlinear program for computing the optimal controller strategy and present two algorithms. First, we propose an exact algorithm that computes the optimal control strategy with probability one but without guarantees on the convergence rate. Second, we present an approximate algorithm that computes a suboptimal control strategy. The approximate algorithm converges faster compared to the exact algorithm; however, it only returns an optimal solution when the adversary has full observation over the controller's strategy. A numerical case study is presented to evaluate the proposed framework.